X-raying the evolution of SN 1987A. Issue Volume 12:Issue S331(2017) (17th October 2017) - Kashyap, Vinay L.; van Dyk, David; McKeough, Katy; Primini, Frank; Jerius, Diab; Gowrishankar, Akshay; Siemiginowska, Aneta; Zezas, Andreas
Abstract: SN 1987A has been observed with the Chandra X-ray Observatory over the entire course of the mission. We have re-analyzed the archival data by constructing an empirical point spread function and reconstructing high-resolution images using a Bayesian multi-scale image reconstruction algorithm. We are able to resolve structure in the equatorial ring of SN 1987A with unprecedented detail, at scales of ≈ 14 arcsec. We describe how the point spread function is constructed, and the reconstruction method, and explore the evolution of the inner ring at different epochs and passbands.